Using Mobile Assisted Language Learning (MALL) to Teach English in Indonesian Context: Opportunities and Challenges - Solihin Solihin (VELES Voices of English Language Education Society, 2021)
Information Technology (IT), more particularly, mobile devices and applications are getting more and more popular in the world of education. Language learning has become one part of education that uses mobile technology. In Indonesia, Mobile Assisted Language Learning (MALL) has been applied in a number of regions although it is also admitted that some places are not as fortunate as those which have applied it. Some have questioned the possibility of the application of MALL in their regions, but some others comment that the application of it is unavoidable. The questions raised in this research are: 1) what are the opportunities as well as the challenges of using MALL?  2) How is the possibility of applying MALL in Indonesian context? This research is descriptive qualitative. The techniques of data collection applied were library research and self-reflection. The data analysis methods were data reduction, data display, and conclusion drawing. To answer the questions in this research, this paper looks at a number of mobile devices and applications and reviews literature (including peer-reviewed articles) related to the opportunities as well as their challenges of incorporation into the context of English as Foreign Language (EFL) education. Their use in Indonesian context is then discussed. Finally, this paper recommends that MALL should be used in EFL education in Indonesia in order to keep up with the digital learning of this world and also suggests that further research should be conducted for each mobile device and app in all parts of Indonesia, including rural areas.